Waste glass catalyst for biodiesel production from waste chicken fat: Optimization by RSM and ANNs and toxicity assessment. (1st May 2021) - Foroutan, Rauf; Mohammadi, Reza; Ramavandi, Bahman
Graphical abstract: Highlights: A waste glass catalyst was used to biodiesel production from waste chicken. Physicochemical properties of the catalyst and biodiesel were characterized. RSM was able to optimize the data better than ANN. Biodiesel fulfil most significant European EN14214 standard properties. The produced biodiesel had no effect on the growth of two bacteria and bean plant. Abstract: In the current study, a heterogeneous solid base catalyst was manufactured by the reaction of waste glass with NaOH and used to generate biodiesel from chicken fat. The surface technical methods were used to characterize the produced catalyst. The active phase in the catalyst was Na2 SiO3 . The data showed that the catalyst is efficient to produce biodiesel from chicken fat (90% efficiency up to fourth stages of reuse). The effect of important variables such as reaction time, temperature, catalyst content, and methanol to oil ratio on the biodiesel production efficiency was optimized by RSM-CCD and artificial neural network (ANN). Maximum biodiesel production was calculated as 98.77% and 97.74% using RSM-CCD and ANN, respectively. The quality of the produced biodiesel was checked by ASTM D 6751 and EN 11214 standards. Also, the produced biodiesel was not toxic to plant and microorganisms and it is a biocompatible fuel.